1983
DOI: 10.1300/j010v08n04_06
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Connection with Self-Help Groups in Health Care Settings

Abstract: The growth of self-help groups relating to health and mental health agencies has been a significant phenomenon of the past decade. Self-help groups offer important benefits to their members as they provide a structure for mutual aid and support and a forum for social/legislative action around a felt social problem. As therapeutic and physical extenders of services they are of significance to professional providers. This paper provides a framework for the professional social worker to view the self-help phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The benefits of group approaches in helping relatives of mentally ill patients to obtain information, share their concerns, and obtain mutual support has been well recognized (Atwood & Williams, 1978;Plummer, Thomton, Seeman, & Littmann, 1981). This has given rise to an increased interest in support groups (Lurie & Shulman, 1983;Neuman & Halvorjon, 1983). Despite this information and need, too few treatment programs offer a comprehensive approach to families and patients that includes education and support groups.…”
mentioning
confidence: 99%
“…The benefits of group approaches in helping relatives of mentally ill patients to obtain information, share their concerns, and obtain mutual support has been well recognized (Atwood & Williams, 1978;Plummer, Thomton, Seeman, & Littmann, 1981). This has given rise to an increased interest in support groups (Lurie & Shulman, 1983;Neuman & Halvorjon, 1983). Despite this information and need, too few treatment programs offer a comprehensive approach to families and patients that includes education and support groups.…”
mentioning
confidence: 99%
“…Many studies (Hatsfield, 1981;Lurie and Schulman, 1983;Black and Drachman, 1985;Gareth, 1989;Nash, 1990;Ma et a]., 1990;Chan et al, 1992) have found that, under a sclf-help cnvironrnent, disabled peoplc can feel better by sharing their experiences with othcr people in similar conditions. taken together, now rcpresent a significant feature of the contemporary health service arena.…”
Section: Self-he@ Approachmentioning
confidence: 99%
“…SELF-HELP GROUPS In tracing the relationship between health professionals and selfhelp groups, Lurie and Shulman (1983) pointed to the role that social workers played in the development of mutual aid societies in the 19th century in helping immigrants with settlement problems. As applied psychology flourished, mental and emotional difficulties were turned over to an increasing array of mental health professionals.…”
Section: The Professions Andmentioning
confidence: 99%